2D Arsenene and Arsenic Materials: Fundamental Properties, Preparation, and Applications. Issue 9 (30th November 2021) - Hu, Yi; Liang, Junchuan; Xia, Yuren; Zhao, Cheng; Jiang, Minghang; Ma, Jing; Tie, Zuoxiu; Jin, Zhong
Abstract: As emerging 2D materials, arsenene and arsenic materials have attracted rising interest in the past few years. The diverse crystalline phases, exotic electrical characteristics, and widespread applications of 2D arsenene and arsenic bring them great research value and utilization potential. Herein, the recent progress of 2D arsenene and arsenic is reviewed in terms of fundamental properties, preparation, and applications. The fundamental properties of 2D arsenene and arsenic, including the crystal phases, environmental stability, and electrical structure, from theoretical to experimental reports are first summarized. Then, the experimental processes for preparing 2D arsenene and arsenic, along with their respective advantages and disadvantages, are introduced including epitaxial growth, mechanical exfoliation, and liquid‐phase exfoliation. Moreover, applications of 2D arsenene and arsenic are discussed, suggesting a wide range of applications of 2D arsenene and arsenic in field‐effect transistors, sensors, catalysts, biological applications, and so on. Finally, some perspectives about the challenges and opportunities of promising 2D arsenene and arsenic are provided. This review provides a helpful guidance and stimulates more focus on future explorations and developments of 2D arsenene and arsenic. Abstract : 2D arsenene and arsenic materials are an essential member of pnictogens. To accommodate the rapid progress of 2D arsenene and arsenic materials, its recent advances from perspectives of fundamental properties, preparation, and applications are reviewed. Finally, current challenges are summarized and a perspective on the further development of 2D arsenene and arsenic materials are made.